Uji Aktivitas Antiplatelet Ekstrak Etanol Kubis Merah (Brassica oleracea var. capitata L.) Antiplatelets activity of red cabbage ethanolic extract (Brassica oleracea var. capitata L.) - Rizki Rica Rachim Fadilah Putri; Evi Umayah Ulfa; Rini Riyanti (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Antiplatelet aggregation effect of red cabbage ethanolic extract (Brassica oleracea var. capitata L.) was measured by bleeding time on Balb-C mice. The test substances given orally during the period of 8 days. Bleeding time was measured on first day and 9th day. Red cabbage ethanolic extract were divided into 3 doses: wich are 9.69 mg/kg body weight; 19,38 mg/kg body weight, and 38,76 mg/kg body weight. After getting the percentage of bleeding time increase, data were analyzed by analysis of variance test (Anova), followed by individual comparison within the groups by LSD test. The test substances above respectively increased bleeding time 58 ± 16%; 70,7 ± 8,9 %, and 113 ± 12%. As the conclusion, red cabbage ethanolic extract doses 38,76 mg/kg body weight could increase bleeding time as well as positive controle 129 ± 8,2%. Keywords: antiplatelets, Brassica oleracea red cabbage, bleeding time.